The prevalence of the mutation in codon 249 of the P53 Gene in Patients with Hepatocellular Carcinoma (HCC) in Turkey - EREN, FATİH (Humana Press Inc., 2010)
Hepatocellular carcinoma (HCC) is one of the most common cancers in the worldwide. Aflotoxins, products of Aspergillus Flavus found in the high humidity environments induce HCC in humans by causing mutations in oncogenes such as codon 249 mutation of p53 in hepatocytes. In turkey, aflatoxins are found to be increased in some foods in certain areas, such as Istanbul which have high humidity. In present study we aimed to look for the prevalence of codon 249 mutation of p53 in patients with HCC, cirrhosis and chronic hepatitis B (CHB). Methods DNA was extracted from plasma and mutation was detected by PCR-RFLP method. Results the codon 249 mutation of p53 is found one out of 50 HCC (2%) patients. In conclusion, although codon 249 mutation of p53 gene has been found very rare but it exists showing the effect of aflatoxins in HCC patients in Turkey. © Springer Science+Business Media, LLC 2010.
Keywords: Aflatoxin; Chronic hepatitis B; Cirrhosis; Hepatocellular cancer; P53 codon 249